Modafinil: a novel alternative to non-invasive ventilation in hypercapnic respiratory failure? - Matos P; Esquinas AM (International Journal of COPD, 2015)
Paulo Matos,1 Antonio M Esquinas2 1Pneumology Department, Hospitais da Universidade de Coimbra, Coimbra, Portugal; 2Intensive Care Unit, Hospital Morales Meseguer, Murcia, SpainNowadays non-invasive ventilation (NIV) is a common therapeutic option in chronic hypercapnic respiratory failure, especially in chronic obstructive pulmonary disease (COPD).1 Even though there is not robust data showing mortality or morbidity benefits, it appears to improve quality of life and reduce admissions for exacerbation.1,2 However, there will always be a group of patients where NIV is not an option, because of poor compliance or side effects. Read the original article